Characteristics of social drinkers with and without a hangover after heavy alcohol consumption - Hogewoning A; Van de Loo AJAE; Mackus M; Raasveld SJ; De Zeeuw R; Bosma ER; Bouwmeester NH; Brookhuis KA; Garssen J; Verster JC (Dove Medical Press, 2016)
A Hogewoning,1,* AJAE Van de Loo,1,* M Mackus,1 SJ Raasveld,1 R De Zeeuw,1 ER Bosma,1 NH Bouwmeester,1 KA Brookhuis,2 J Garssen,1,3 JC Verster1,4 1Division of Pharmacology, Utrecht University, Utrecht, 2Faculty of Behavioral and Social Sciences, Groningen University, Groningen, 3Nutricia Research, Utrecht, the Netherlands; 4Centre for Human Psychopharmacology, Swinburne University, Melbourne, VIC, Australia *These authors contributed equally to this work Background: A number of social drinkers claim that they do not experience next-day hangovers despite consuming large quantities of alcohol. The aim of this study was to investigate the characteristics of drinkers who claim to be hangover immune and compare them with drinkers who do report having hangovers. Methods: A total of 36 social drinkers participated in a naturalistic study consisting of a hangover day (alcohol consumed) and a control day (no alcohol consumed). Data were collected on alcohol consumption, demographics, sleep, next-day adverse effects, and mood. Data from drinkers with a hangover (N=18) were compared with data from drinkers who claim to be hangover immune (N=18). Results: Drinkers with a hangover reported drowsiness-related symptoms, symptoms related to reduced cognitive functioning, and classic hangover symptoms such as headache, nausea, dizziness, weakness, and stomach pain. Corresponding mood changes comprised increased feelings of depression, anger–hostility, fatigue, and reduced vigor–activity. In contrast, hangover-immune drinkers reported relatively few hangover symptoms, with only mild corresponding severity scores. The reported symptoms were limited to drowsiness-related symptoms such as sleepiness and being tired. The classic hangover symptoms were usually not reported by these drinkers. Conclusion: In contrast to drinkers with a hangover, for those who claim to be hangover immune, next-day adverse effects of alcohol consumption are limited to a mild increase in drowsiness-related symptoms. Keywords: alcohol, hangover, symptoms, mood, immunity